Fuel Application Efficiency in Ideal Cycle of Gas Turbine Plant with Isobaric Heat Supply - A. P. Nesenchuk; A. V. Begliak; T. V. Ryzhova; D. I. Shklovchik; V. V. Begliak; A. A. Abrazovsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper reveals expediency to use in prospect fuels with maximum value  Qнр∑Vi and minimum theoretical burning temperature in order to obtain maximum efficiency of the ideal cycle in GTP with isobaric heat supply.